Building an Arabic digital collection: the IIUM Library’s experience - Abdullah, Sarifah (Springer, 2006)
The IIUM Library’s mission is to be an excellent information centre providing information to meet the learning, teaching, and research needs of its customers. The Library gives special attention to Islamic studies and its information resources are predominantly in English and Arabic. To make the resources readily accessible “anytime” and “anywhere” heavy investments were made in a digital library system that implements the latest ICT advancement. The need for Arabic language capabilities has always been one of the Library’s major requirements. This paper shares the Library’s experience in implementing a digital library system, focusing on the challenges in handling Arabic language information resources.